Treatment recommendations as complex activities: A sequential unfolding of acceptance - Weidner, Matylda (Papers in Linguistics, 2025)
This paper offers empirically grounded observations on the interactional organization of treatment recommendations in secondary care in the context of Polish healthcare. Drawing on conversation analysis as a method of analysis, the paper highlights practices involved in the design of the activity of recommending treatment. It begins with a background sketch of the available interactional research on the organization of treatment recommendations in Polish doctor-patient communication, followed by a case study that focuses on the format in which invasive treatment recommendation is presented and the sequential unfolding of patient’s acceptance thereof. The paper concludes that patients and doctors use joint interactional strategies to manage the progressivity of the treatment recommendation activity towards a mutually agreeable and acceptable outcome.